2022
DOI: 10.3390/cancers14030781
|View full text |Cite
|
Sign up to set email alerts
|

Value of Targeted Biopsies and Combined PSMA PET/CT and mp-MRI Imaging in Locally Recurrent Prostate Cancer after Primary Radiotherapy

Abstract: Radiorecurrent prostate cancer is conventionally confirmed using systematic and/or targeted biopsies. The availability of multiparametric (mp) MRI and prostate specific membrane antigen (PSMA) PET/CT has increased diagnostic accuracy. The objective was to determine the positive predictive value (PPV) of combined mp-MRI and PSMA PET/CT and whether pathology verification with MR-targeted biopsies remains necessary for patients with radiorecurrent prostate cancer. Patients with locally recurrent prostate cancer w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…PET with MR imaging can provide diagnostic confidence. It has been suggested that in patients with questionable recurrent prostate cancer post radiation therapy, if both PSMA PET and MRI are positive, given nearly 100% PPV, biopsy confirmation may not be needed [51 ▪ ].…”
Section: Pet Imagingmentioning
confidence: 99%
“…PET with MR imaging can provide diagnostic confidence. It has been suggested that in patients with questionable recurrent prostate cancer post radiation therapy, if both PSMA PET and MRI are positive, given nearly 100% PPV, biopsy confirmation may not be needed [51 ▪ ].…”
Section: Pet Imagingmentioning
confidence: 99%
“…PSMA PET/CT may improve patient selection for salvage focal ablation through greater ability firstly to rule out distant disease, and secondly to rule in local recurrence in conjunction with mpMRI [24,25]. When using both 68 Ga-PSMA-11 PET/CT and mpMRI, one study found a positive predictive value of 98% with targeted biopsy [26]. PET/MRI and whole-body MRI are also emerging tools that warrant further study [27,28].…”
Section: Future Directionsmentioning
confidence: 99%
“…castration resistant prostate cancer) usually occurs within 1-3 years after start of hormonal treatment, requiring further systemic treatment with for example second-line hormonal treatment or chemotherapy. 29,[78][79][80] Local treatment for recurrent prostate cancer…”
Section: Locally Recurrent Prostate Cancermentioning
confidence: 99%
“…75,77 However, pathological assessment of biopsies is problematic given the risk of false negatives due to sampling errors and radiation effects hindering accurate classification. 78,79 In a study by Rasing et al 80 the positive predictive value of combined mp-MRI and PSMA-PET/CT for detecting recurrent prostate cancer was 97.6% in 41 patients treated with FS-HDR-BT, indicating the limited added value of targeted biopsies in these patients. However, these results are only valid for those in whom mp-MRI and PSMA-PET/CT are concordant.…”
Section: Identification Of Recurrent Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation